An investigation of building occupants behaviour during fire alarm - Alao Mohammed Kaseem,; Yahya Mohamad Yatim,; Wan Yousuf Wan Mahmood, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The safety of building occupants during fire emergencies depends mainly on the occupant's behavior in the fire event. Therefore, this study investigates the behavior of high–rise building occupants in Nigeria when they hear the sound of fire alarm under fire drill. The study adopted a survey research design. The population for this study consists of 349 low and high-rise building occupants across six north-central state of Nigeria. A research question was used to direct the study. A structured questionnaire was used to collect data from the respondents which was duly validated by an expert in the field of fire safety. Cronbach Alpha reliability technique was used to determine the internal consistency of the questionnaire items at 0.90. Data collected were analysed through confirmatory factor analysis (CFA) using Statistical Package for Social Sciences (SPSS) and Analysis of Moment of Statistics (Amos). After a preliminary analysis (descriptive), data from respondents were found suitable for presence in confirmatory factor analysis (CFA), The CFA was performed, and results of the analysis support the one-factor model of occupants behavior in building when they hear the sound of the alarm during a building fire can enhance early evacuation and safety of lives and properties. The study found that occupants required nine actions to be taken when they hear the sound of fire alarm under investigation. However, the study recommended that fire training; total compliance with the relevant fire safety regulations, fire drill, fire communication, and effective fire safety management should be organized for the high or low-rise building occupants to enhance their knowledge of fire safety in a building.